USING ADBUSTING TECHNIQUE TO IMPROVE STUDENTS’ WRITING SKILL - Fitri Novia (Language and Education Journal, 2018)
Writing is an important subject which needs to be taught from elementary to university level. However, students still get difficulties in doing writing activities. Adbsuting technique can be used to improve students’ problems in writing skill. Therefore, the objective of this study was to find out whether or not adbusting technique could improve students’ writing achievement. A classroom action research (CAR) was used in this study as the method. The participants were second-semester students of English major of FKIP UNISKI Kayuagung which consisted 26 students. To collect the data written test was used. The students chose one of the topics which consisted five topics then they wrote a paragraph based on the topic. Mean score was used to analyze the data. Based on the result, the mean score of students on writing before the treatment was 60. The mean score of post test 1 at the first cycle was 66,58. The mean score of post test 2 at the second cycle was 74,15. The mean score of post test 3 at the third cycle was 80.92. Thus, the data showed that adbusting technique could improve students’ writing achievement